Penyusunan Laporan Keuangan UMKM Berdasarkan SAK EMKM Berbantuan Microsoft Excel - Nisrina Nur Rohmah; Hastuti (Indonesian Accounting Literacy Journal, 2021)
MSMEs (Micro, Small and Medium Enterprises) have a fairly important role in developing the economy in Indonesia. Unfortunately, until now there are still problems that cause MSMEs to not develop optimally, one of the reasons is the lack of attention to the importance of compiling financial reports. Whereas financial reports will be very useful for evaluating the performance of MSMEs. The purpose of this study is to determine the financial records that have been carried out by MSME Skinka, then design financial reports with Microsoft Excel and prepare financial reports based on SAK EMKM. The research method used is descriptive qualitative method. Data collection techniques were carried out by interview and documentation. The preparation of financial statements is made in accordance with SAK EMKM which consists of a profit and loss statement, balance sheet and notes to financial statements.